Primary intramuscular hydatid cyst over the back: A rare presentation of echinococcosis (Indian Journal of Case Reports, 2018)
Hydatid disease is often manifested as a slowly growing cystic mass, with hepatic and pulmonary involvement being most common. Unusual sites of involvement frequently cause diagnostic problems, and hence, delay in diagnosis and many serious complications. In endemic areas, cystic lesions anywhere in the body, in appropriate patient group, should be evaluated for hydatid disease. We report an unusual case of primary hydatidosis of the back muscle, in which a wide excision was performed without causing any damage to the cyst wall. Injudicious approach in the management of these rare presentations may be the root cause of severe anaphylactic shock and systemic dissemination. Intramuscular hydatid cysts grow gradually and may mimic a soft tissue tumor; thus, the diagnosis of soft-tissue hydatid cysts needs a high index of suspicion.